مشروع مذكرة التخرج - سليماني ، نورالدين (Mohamed Boudiaf University of M'Sila, 2023)
الملخص : المطبوعة موجهة لطلبة السنة الثالثة ليسانس قسم التربية البدنية بمعهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة المسيلة حيث تناولت المطبوعة العناصر الأساسية لخطة البحث متمثلة في مقدمة البحث والتعريف بمحتوياته النظرية ومتغيراته الأساسية مراجعة الدراسات السابقة والمشابهة وتحديد الجديد في البحث و الدراسة الاستطلاعية وصياغة مشكلة البحث والتساؤلات الجزئية و صياغة الفرضيات (الفرضية العامة والجزئية(وتحدٌيد أهداف وأهمية البحث وتحديد المفاهيم والمصطلحات الأساسية واختيار المنهج العلمي الملائم والمناسب للبحث مع تحديد المجتمع الأصلي للبحث وعينة البحث الأساسية وكيفية اختيارها وأدوات جمع المعلومات وكفية بنائهاوتحليل البيانات والمعالجة الإحصائية. Abstract The publication is directed to third-year students of the Department of Physical Education at the Institute of Sciences and Techniques of Physical and Sports Activities at the University of M'sila. The publication dealt with the basic elements of the research plan, represented in the introduction to the research and defining its theoretical contents and basic variables, reviewing previous and similar studies, identifying new things in the research, exploratory study, formulating the research problem and partial questions, formulating hypotheses (general and partial hypothesis), defining the objectives and importance of the research, defining the basic concepts and terms, choosing the appropriate scientific method for the research, identifying the original community for the research, the basic research sample, how to choose it, tools for collecting information, and how to build it, data analysis and statistical processing.
Keywords: مذكرة التخرج; التربية البدنية; المنهج العلمي